Antimicrobial resistance of Salmonella enterica in pork and vegetable servings at pork joints in Kampala, Uganda - Ndoboli, D.; Heilmann, Martin; Roesel, Kristina; Clausen, Peter-Henning; Wampande, E.; Grace, Delia; Alter, T.; Huehn, S. (International Livestock Research Institute, 2016)
The aim of this study was to investigate the prevalence and antimicrobial resistance of Salmonella enterica subsp. enterica serovars including the presence of shared plasmids in pork and related fresh vegetables served in pork joints in Kampala, Uganda. Pork butcheries in three of the five administrative divisions of Kampala were included for the survey. Samples included raw pork, roasted pork, water, onions, tomatoes, cabbage, butcher’s hands (swabs), utensils (swabs) and fly midgut extracts. A total of 693 samples were collected from 77 pork butcheries from June- October 2014. Overall 53.2% pork joints had samples positive for Salmonella enterica subsp. enterica serovars. Isolation rates ranged from 31.2% (24/77) for raw pork, 1.3% (1/77) for roasted pork, 7.8% (6/77) for tomatoes, 2.6% (2/77) for onions, 5.2% (4/77) for cabbage, 9.1% (7/77) in water, and 22.1% (17/77) from fly midguts. Swab samples taken from utensil and butcher’s hands swabs were found negative (Heilmann et al., 2015). In the isolates obtained, resistance towards 22 antibiotics was tested. Resistances were found towards 11 out of the 22 antibiotics tested. High resistances were found to Cephazolin (97%), Cefotixime (93%), Gentamicin (88%), and Ceftazidime (86%). Intermediate resistance was found to Ciprofloxacin (59%) and Amoxicillin-Clavulanic acid (57.6%). Most isolates (85%) were susceptible to Levofloxacin, Ofloxacin, Sulfamethoxazole and Trimethoprim. Identification of plasmids by PCR-based replicon typing was performed recognizing FIA,FIB,FIC,HI1,HI2,I1- 1ᵞ,L/M,N,P,W,T,A/C,K,B/O,X,Y,F and FIIA. Six incompatibility groups were identified: FIA, W, FIC, FIB, P, Y with more than one incompatibility group existing among different isolates. A high resistance rate among Salmonella strains was found while the total number of incompatibility groups detected was with approximation 2.4. Thus, even though the total number of plasmids per strain is low, resistance rates detected remain high. The high resistance rates are probably resulting from intensified food animal production driving a greater use of antibiotics, which is a crucial aspect of public health concern.